Assessment of quality of life in Turkish patients with cancer - (:unkn) unknown (My University, 2003)
We evaluated Quality of Life (QOL) in cancer patients by using the Turkish version of Multidimensional Quality of Life Scale-Cancer 2. Data were analysed for 188 consenting individuals with mean age 49.7 (SD=15.9) years, most of whom were male, married, primary school educated and treated by combined therapy. The interesting finding of this study was that sociodemographic factors rather than cancer-related factors could contribute to poorer QOL. In this study we showed that duration of the disease and type of cancer, presence of metastasis, and type of treatment had no effect on QOL. However, age, educational level, and hospitalization were associated with particular domains of QOL. Subjects with older age reported lower QOL in all subdimensions. Significant differences existed in subscales of QOL and total QOL among the patients who had different educational level. Illiterate patients had the lowest QOL scores except nutrition. Hospitalized patients had lower QOL scores than patients treated on an outpatient-basis. In conclusion, health workers who work with cancer patients need to determine the underlying reasons of the patient's QOL and evaluate the impact of sociodemographic variables.
Keywords: Cancer patients; MQOLS-CA2; Quality of life